Plasmon coupled 2D random medium For Enhanced absorption in solar cells - Bingi, Jayachandra (2015)
Random textures are proved to be better for energy harvesting in solar cells. In this research, we have studied the absorption properties of a random dielectric medium with plasmonic nanostructures in it. This structure has shown significant enhancement in broad band absorption of light spectrum and higher extinction of near infrared wavelengths. We also discuss several strategies to improve the solar cell efficiency based on dielectric and plasmonic random media. Finally, a comparative study of solar cell efficiencies with flat, periodic and random structures as active medium and back reflectors is carried out with a proposal for possible potential solar cell configurations.